2009
DOI: 10.1111/j.1759-6831.2009.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and ontogeny of unisexual flowers in dioecious Woonyoungia septentrionalis (Dandy) Law (Magnoliaceae)

Abstract: Woonyoungia septentrionalis (Dandy) Law is a dioecious species with unisexual flowers in Magnoliaceae. The floral morphology and structure of the species are conspicuously different from other species and are important to the study of floral phylogeny in this family. The floral anatomy and ontogeny were investigated to evaluate the systematic position of W. septentrionalis, using scanning electron microscopy and light microscopy. All of the floral organs are initiated acropetally and spirally. The carpels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the staminate flowers of Knema examined, we found that the central area of the floral apex, where a gynoecium normally develops, remains undifferentiated. However, in the species of Magnoliaceae with unisexual flowers, there is a carpel residuum in the staminate flowers, which indicates the sex change (Fu et al ., 2009). In unisexual Annonaceae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the staminate flowers of Knema examined, we found that the central area of the floral apex, where a gynoecium normally develops, remains undifferentiated. However, in the species of Magnoliaceae with unisexual flowers, there is a carpel residuum in the staminate flowers, which indicates the sex change (Fu et al ., 2009). In unisexual Annonaceae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Eames ( 1931 ) once stated that the primitiveness of this kind of carpel is unequivocal. Detailed studies on the gynoecia in the Magnoliaceae have demonstrated that this oversimplification cannot be corroborated (Tucker 1961 ; Eyde 1975 ; Tucker 1975 ; Ueda 1982 ; Endress et al 2000 ; Xu and Rudall 2006 ; Fu et al 2009 ; Deroin 2010 ). Furthermore, the traditional phylogenetic position of the Magnoliaceae as sister to remaining angiosperms (Cronquist Magnolialean hypothesis; Cronquist 1988 ;) is no longer tenable and has been replaced by the APG system (Qiu et al 1999 ; Hilu et al 2003 ; APG 2009 ; Chase and Reveal 2009 ; Vialette-Guiraud and Scutt 2009 ; Soltis et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The other disjunct region is in southeastern Yunnan (Yang, Guo & Zailiu, 2018 ). Due to its restricted geographic distribution, high habitat specificity, and slow natural regeneration (Fu et al., 2009 , 2012 ; Ling et al., 2021 ), M . kwangsiensis has been listed in the Class I National Key Protected Wild Plant List of China ( https://www.forestry.gov.cn/ ).…”
Section: Introductionmentioning
confidence: 99%